Analisis Tujuan dan Kurikulum Pendidikan Islam dalam Perspektif Harun Nasution & Fazlur Rahman - Syaiful Dinata; Eva Latipah; Ismatul Izzah (Universitas Negeri Padang, 2023)
Education is a very significant aspect to educate the nation's children which is developed all aspects of education, one of which is the purpose of Islamic education and the Islamic education curriculum. The purpose of this study is to analyze the objectives of Islamic education and the Islamic education curriculum from the perspective of Harun Nasution and Fazlur Rahman. This study uses a type of qualitative research with an analytical content design. The data collection technique in writing this scientific paper is a documentation technique, namely data collection by selecting data that correlates with the title of the study. The method of documentation on this writing is by collecting data, analyzing data according to the theory to obtain conclusions. The results of this study show that these two figures' thoughts are interrelated with each other. (i) From the purpose of Islamic education, where Harun is centered on the practice of knowledge and boils down to a cultured noble mind, then Rahman focuses on the cultivation of a creative personality and also boils down to good morals in order to create order and peace. (ii) these two figures' thoughts are so relevant to be realized today, because the curriculum concepts that these two figures present are also very modern and very in line with the problems of the Islamic education world. (iii) The development of increasingly modern technology, does not make the concepts described by Harun and Rahman also lag behind, but the thoughts of these figures who will answer the challenges of technological developments for the world of education. Thus, the thinking of these two figures is immediately possible to be applied to improve the system of Islamic education.